Learning to argue in mathematics: effects of heuristic worked examples and CSCL scripts on transactive argumentation - Vogel, Freydis; Reichersdorfer, Elisabeth; Kollar, Ingo; Ufer, Stefan; Reiss, Kristina; Fischer, Frank (International Society of the Learning Sciences, 2013)
A previous study has shown that both CSCL scripts and heuristic worked examples implemented in a CSCL environment were effective to fostering students' acquisition of argumentation skills in the context of mathematical proof tasks (Kollar, et al. 2012). This paper investigates the extent to which transactive argumentation during the collaborative learning process can be evoked by both means of instructional support and to what extent transactive argumentation mediates their effects on students' knowledge about argumentation. We present process measures from a 2x2-factorial experiment with the factors CSCL script and heuristic worked examples conducted with N=101 prospective math teacher students. Results show that both means of instructional support induced transactive argumentation in the collaborative learning process. The self-generated transactive argumentation, but not the partner-generated transactive argumentation mediated the effects of both types of instructional support on students' development of argumentation knowledge. Nevertheless, the learning partners mutually influenced their transactive argumentation.